Advanced conceptual design for the regasification process to minimize carbon emissions, water use, and reduce operating costs for AI data centers, airport hubs, smart cities and initial zero-emission LNG receiving terminals - Sermsuk, Maytungkorn; Sukjai, Yanin; Rajoo, Srithar; Kiatkittipong, Kunlanan; Wiboonrat, Montri; Siripongdee, Surapong (My University, 2026)
Achieving net-zero greenhouse gas emissions by 2050 requires improving energy efficiency in transitional fuels such as liquefied natural gas (LNG). In 2023, global LNG imports reached 401.5 MTPA; however, most of the 180 LNG receiving terminals worldwide still discharge large amounts of recoverable cold energy into the ocean. Meanwhile, the rapid growth of artificial intelligence (AI) data centers is driving unprecedented electricity demand, with projected global electricity consumption exceeding 3000 TWh by 2030. This study proposes an advanced LNG regasification system integrating Intermediate Fluid Vaporization (IFV), Rankine Cycle (RC), and Direct Expansion Cycle (DEC) to recover both temperature and pressure exergy. The system is evaluated for LNG terminals with capacities of 10–30 MTPA under pressure levels of 70, 30, and 6 bar across eight operational models and two infrastructure configurations. Results indicate that terminal electricity imports are reduced by 52–78 % compared with conventional open rack vaporizer (ORV) systems. Net electricity generation ranges from 12.09 to 197.91 MW, while chilled water cooling capacity reaches 272.72–1075.44 MW. Cooling electricity demand is reduced by approximately 79 %, lowering data center Power Usage Effectiveness (PUE) from 2.00 to 1.36. Water Usage Effectiveness (WUE) decreases from 1.9 to 3.0 to approximately 0.3 L/kWh, achieving an 89–93 % reduction in cooling-related water use. At 30 MTPA, carbon emissions are reduced by up to 2.99 million tons annually, with economic savings of USD 119.96–603.15 million per year and a maximum IRR of 37.7 %. These results demonstrate the significant potential of LNG cold energy integration for near-zero-emission terminal operation and sustainable data center cooling.
Keywords: Carbon emissions; Cold energy utilization; cold recovery; Data center; District cooling; Liquefied natural gas (LNG)